Qualitative Consumer Research on Acceptance of Long-Acting Pre-Exposure Prophylaxis Products Among Men Having Sex with Men and Medical Practitioners in the United States - Calder, Bobby J. (AIDS Res Hum Retroviruses, 2018)
Pre-exposure prophylaxis (PrEP) with oral Truvada(®) prevents HIV infection. However, the adherence to pill taking required for efficacy has sparked interest in developing new antiretroviral delivery systems that decrease such demands. Long-acting formulations, such as injections and implants, represent promising options that require less frequent adherence. It is important, however, that development of these new modalities be driven by understanding of the value seen in them by target users to maximize their uptake. To identify the key product features that impact user acceptance, we used a three-phase marketing research approach. In this study, we describe the results of the first-phase, qualitative focus group research performed in Chicago and San Francisco that explored subjective perceptions of oral versus alternative PrEP modalities among men having sex with men (MSM) and medical practitioners caring for MSM. Data revealed that potential value in long-acting PrEP lies more in simplifying the lives of users rather than in making them more confident in their adherence. The results provide an important guidance for designing and promoting these future long-acting products to enhance their contribution to increasing the current limited uptake of PrEP that will better stem the HIV epidemic.